Enabling environments for e-mobility and renewable energy integration in Southeast Asia - Dixon, J; Zhou, Z; Hirmer, S; Chiang, P (Zenodo, 2022)
Deep and drastic cuts of greenhouse gas emissions are urgently needed from all sectors of the global economy to avoid irreversible climate and ecological breakdown. The majority of transport decarbonization pathways rely on two parallel activities: (i) the electrification of the majority of modes of surface transport, including road and rail, and even short-distance shipping and aviation; and (ii) significant growth in renewable electricity generation. Making this work effectively will require the interaction of two previously siloed sectors: electricity and transport. This working paper explores how relevant stakeholders can support enabling environments for the integration of e-mobility and renewable energy in the Southeast Asian context, based on analyzed interviews with staff of energy and transport secretariats of the Asian Development Bank and United Nations Environment Programme.